2022
DOI: 10.3389/fncel.2022.983298
|View full text |Cite
|
Sign up to set email alerts
|

Brain tissue oxygen dynamics while mimicking the functional deficiency of interneurons

Abstract: The dynamic interaction between excitatory and inhibitory activity in the brain is known as excitatory-inhibitory balance (EIB). A significant shift in EIB toward excitation has been observed in numerous pathological states and diseases, such as autism or epilepsy, where interneurons may be dysfunctional. The consequences of this on neurovascular interactions remains to be elucidated. Specifically, it is not known if there is an elevated metabolic consumption of oxygen due to increased excitatory activity. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
(68 reference statements)
1
2
0
Order By: Relevance
“…Specifically, PTX administration resulted in an increase in power across most frequency bands, with a pronounced enhancement in the lower frequency ranges (<20 Hz). These findings are consistent with previous studies showing that PTX can increase lower frequency power in the LFP spectra, even at lower concentrations [ 33 ]. Moreover, an increase in gamma band EEG activity has been reported at higher PTX doses [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, PTX administration resulted in an increase in power across most frequency bands, with a pronounced enhancement in the lower frequency ranges (<20 Hz). These findings are consistent with previous studies showing that PTX can increase lower frequency power in the LFP spectra, even at lower concentrations [ 33 ]. Moreover, an increase in gamma band EEG activity has been reported at higher PTX doses [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…The direct and indirect pathways of preventing hypoxia likely work together to prevent hypoxia. This was demonstrated in a recent study which observed transient, severe drops in oxygen concentrations after the administration of a GABA antagonist (Aksenov et al, 2022). By mimicking the debilitation of GABAergic signaling, EIB exhibited a significant shift toward excitation, such that there were intermittent spikes in local field potentials, coupled with dramatic drops of tissue oxygen concentrations below 10 mm Hg.…”
Section: Combined Inhibition and Regulation Of Vasomotionmentioning
confidence: 82%
“…Compared to the hemodynamic response, interneurons can play an even more fundamental role in the regulation of BTOO due to their ability to relay resting state activity to vessels via GABA receptors. Indeed, it was shown that blocking GABAreceptors greatly decreases the frequency of BTOO (Aksenov et al, 2022). However, not all interneurons can be responsible 10.3389/fnmol.2022.1069496 for BTOO.…”
Section: Interneurons and Vasomotionmentioning
confidence: 99%